Supercooled liquid phases of luminescent zero dimensional metal halide hybrids - Kumar Das, Deep; Marayathungal, Jumana Hasin; Palakkolil, Athira; Sarma, Dhritismita; Khan, Akram Aadil; Kumar, M. Praveen; Kudlu, Ashwath; Choudhary, Mahendra; Hathwar, Venkatesha R.; Pujala, Ravi Kumar; Mahata, Arup; Kundu, Janardan (Journal of Physical Chemistry Letters, 2025)
Chemical design of metal halide hybrids (MHHs) with suppressed melting point (T-m) allows access to glassy phases from their liquid-melts. Thermal phase change (crystal-melt-glass) properties of glassy MHHs (with glass transition temperature T-g > room temperature) have been exploited for device applications. However, room temperature stable supercooled liquid (SCL) MHHs (with T-g < room temperature), originating from glass-SCL phase change, remain inaccessible. Here, a molecular design strategy is reported to access ambient stable, melt-processable, SCL multimetallic bromide hybrids (Mn2+,Cd2+; Mn2+,Zn2+; Benzyltributylammonium) with low T-g (15-16 degrees C), low T-m (90-100 degrees C), green luminescence, and high optical transparency. Structural, optical, thermal, and computational analyses highlight chemical design principles and support dopant (Mn2+) based luminescence. Rheological measurements confirm the SCL phase that shows thermal hysteresis and estimate relaxation time scales. This work provides a new material platform showcasing enhanced melt-processability for fabrication of moldable devices, unravelling chemical makeup-property correlation and expanding the material phase types of MHHs.

Bright dual-phase organic luminescence from zero-dimensional lead halide hybrids via sensitized thermally activated delayed fluorescence for multifunctional applications - Kumar Das, Deep; Sarma, Dhritismita; Kumar, M. Praveen; Khan, Akram Aadil; Madhusoodhananan, Mahesh; Kudlu, Ashwath; Ajithkumar, Thalasseril Govindankuttykaimal; Pujala, Ravi Kumar; Mahata, Arup; Kundu, Janardan (Chemistry of Materials, 2026)
Metal halide hybrids have long celebrated their halometallate moieties as the luminescent center, leaving organic cations behind. Although the thermally activated delayed fluorescence (TADF) strategy has enabled efficient solid-state organic emitters, the complex molecular design required for TADF emitters has limited their facile integration into metal halide hybrid architectures. Here, we demonstrate a versatile strategy wherein a nonemissive organic moiety (benzyltributylammonium) is incorporated into a zero-dimensional disphenoidal Pb-halide hybrid, [(C19H34N)2PbCl4], resulting in efficient TADF-based dual-phase organic emission sensitized by halometallate units in the solid state (crystalline; amorphous). These materials exhibit strong PLQY (similar to 85%) and tunable organic luminescence (blue emission in crystalline phase; cyan emission in amorphous phase) modulated by the packing extent of organic moiety. [PbX4]2- units act as absorptive centers that sensitize organic cations showing TADF-based strong emission. Ground and excited state density functional theory calculations reveal the unique origin of sensitized TADF organic luminescence. Rheological measurements characterize relaxation dynamics of glass <-> supercooled liquid transitions, establishing correlations between molecular packing, phase, and emission characteristics. This first demonstration of dual-phase, sensitized TADF-based organic luminescence in lead halide hybrids establishes a new design paradigm that bridges molecular and solid-state photophysics, opening avenues for multifunctional applications in LEDs, optical thermometry, and security technologies.